Bilateral Symmetrical Thalamic Lesions: An Infarction Involving the Artery of Percheron - Ewe Jin Koh; Alvin John Gnanasegaran; Ming Lee Chin (Oman Medical Journal, 2025)
The artery of Percheron is a rare anatomical variant artery that supplies the bilateral thalami and midbrain. An acute occlusion of the vessel will lead to the presentation of a bilateral thalamic stroke syndrome. The classical presentation includes somnolence and a reduced level of consciousness. Therefore, this clinical entity often goes unrecognized and diagnoses are usually delayed due to the ambiguity of presenting symptoms. We report a case of a man presenting with an acute onset of drowsiness, later diagnosed with a bilateral thalamic infarct only days later due to the vague clinical symptoms. We also highlighted several key learning points from this case and emphasized the importance of recognizing this syndrome.